The Impact of Mother Tongue on Students’ Speaking Skills - Parawansyah, Azzahra Ellyasari; Sakkir, Geminastiti; Fauzan, Muhammad Miftah (Yayasan Cendekiawan Indonesia Timur, 2026)
This study aims to describe the impact of mother tongue use on students' English-speaking skills in terms of fluency, accuracy, confidence, expression, and response. This study uses a descriptive qualitative approach and was conducted at SMP Negeri 7 Mappakasunggu, Takalar Regency, South Sulawesi. The research subjects consisted of six eighth-grade students selected through purposive sampling based on their tendency to use their mother tongue in English-speaking activities. Data were collected through classroom observation and semi-structured interviews, then analyzed using the interactive analysis model of Miles, Huberman, and Saldana. The results showed that excessive use of the mother tongue had an impact on low fluency, grammatical errors, limited vocabulary, underdeveloped expression, and slow and brief responses. However, this study also found that the mother tongue has a positive and constructive role, particularly in helping students understand the material, formulate ideas before speaking, and increase their sense of security and courage through translanguaging practices. Thus, the mother tongue does not only function as an obstacle, but can also be a source of support for learning to speak English when used in a targeted manner.